Design of a Web-Based Human Resource Monitoring Information System on PT Putra Pratama Jaya Mandiri - Dini, Siti; Supriyanti, Dedeh; Ananda, Zahra (Journal Collabits, 2024)
PT Putra Pratama Jaya Mandiri was established in 2011 located Jl. Bhayangkara 1 No. 1 Paku Jaya, North Serpong, South Tangerang. PT Putra Pratama Jaya Mandiri is a company engaged in Interior Services which has 2 branch offices located in Tangerang and Bali with a total number of employees of 275 employees. Human resource data management or employee management that is currently running is not running well because it is still done using Microsoft excel so that there are still some problems, namely the absence of a system that is used as a container to collect employee work data reports every day so that HR must collect one by one to find out the results of employee work that has been done every month,  There is no application used to support the optimization of employee data (new, resign, mutation, promotion and retirement) specifically in data storage, data security has not been well maintained because it can still be seen by many people. This research produces a web-based employee data system that can help HR in managing employee data (new, resign, mutation, promotion and retirement). In addition, it helps employees inform the results of work reports that have been done so that OM, HR and division heads can control the results of employee work every day. This system is created using the PHP programming language and Mysql database. This research uses the RAD method as system development and blackbox testing for system testing.